Strategy Angklung Extracurricular Learning In SMP 13 Cirebon (Jurnal Seni Musik, 2020)
Angklung learning strategies in SMP Negeri 13 Cirebon are very unique, teachers use not in accordance with their learning. The problem discussed in this paper is how the strategies are used by the trainer and what are the supporting and inhibiting factors. This research uses qualitative. The target of this research is angklung extracurricular learning strategy in SMP Negeri 13 Kota Cirebon. Data collection techniques using observation, interviews, documentation, and triangulation techniques. The results showed that: (1) The trainer used a direct learning strategy; (2) supporting factors are facilities provided; (3) inhibiting factors, namely extracurricular schedules that collide with other extracurricular schedules. The strategy used is a direct learning strategy. students are more focused on the teacher with several methods, namely lectures, demonstrations, and drills. The media used are angklung instruments, keyboards, laptops, amps, and blackboards.